Pelaksanaan PTSL Serta Faktor Penghambat Berdasarkan Permen Agraria/Kepala BPN No 6 Tahun 2018 Tentang PTSL di Kota Bajawa Kabupaten Ngada Nusa Tenggara Timur - Oktavianus Carlos Awa Pea; Agustinus Hedewata; Darius Mauritsius (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
The purpose of this research is to analyze the implementation of Complete Systematic Land Registration (PTSL) and the inhibiting factors based on the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 6 of 2018 concerning (PTSL) in Bajawa City. This research is an empirical legal research conducted at the Ngada Regency Land Office. Data collection techniques using interview techniques and literature / document studies. The data used are primary data, secondary data and tertiary data. This research was conducted in Bajawa City, Ngada Regency, East Nusa Tenggara. The results of data management were analyzed descriptively using qualitative methods. Based on the results of the research and discussion, it can be seen that the Implementation of the Complete Systematic Land Registration (PTSL) Programme in Bajawa City, Ngada Regency, has been running well in the two Villages/Kelurahan Lebijaga and Desa/Kelurahan Bajawa both seen from the achievement of the 2022 programme target. The inhibiting factor in the Ngada Regency Land Office is that work performance is still not optimal due to the lack of apparatus. Facilities and infrastructure are also still lacking, especially for two-wheeled vehicles and four-wheeled vehicles as well as office equipment such as computers and laptops.